First case of fungal keratitis due to Aspergillus minisclerotigenes in Iran - Mohammad Javad Najafzadeh; Mahmoud Karimizadeh Esfahani; Alireza Eslampoor; Somayeh Dolatabadi; Jos Houbraken (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Herein, we report the first case of fungal keratitis due to Aspergillus minisclerotigenes in a 68-year-old rural woman admitted to the Ophthalmology Center of Khatam-Al-Anbia Hospital in Mashhad, northeast of Iran. Case report: The patient presented with severe pain, burning, foreign body sensation, and reduced vision in her right eye. She had long-term uncontrolled diabetes and was not able to close her eye due to an anatomical problem with the eyelid. The cornea smear sample was cultured, and the fungus was initially identified as Aspergillus flavus. The isolated strain was further identified by sequencing a part of the calmodulin gene as A. minisclerotigenes. The patient did not respond to any antifungal treatments (e.g., amphotericin B and voriconazole drops, and fluconazole 300 mg/day); therefore, she was eventually subjected to corneal transplantation surgery. Conclusion: Fungal keratitis can be caused by the less common species. The reliable identification of the causative agents can be accomplished by the implementation of molecular methods.